DESTINATION MARKETING TO IMPROVE DOMESTIC TOURISTS’ RETURN INTENTION - Filda Rahmiati; Andrean Winata (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2020)
Purpose: This study aims to analyze tourist return intention through destination attribute (attraction, accessibility, and amenities), promotion, and destination image mediated by tourist satisfaction. Research methods: The research method used in this research is a quantitative research. This study used 410 respondents who were domestic tourists who had visited Borobudur Temple using purposive sampling. The Partial Least Square-Structural Equation Model (PLS-SEM) used to test hypotheses. Results and discussions: The results of this study indicate that all hypotheses are accepted, that the attributes of the destination (attraction, accessibility, and amenities), promotion, and destination image significantly influence on tourist return intention mediated by tourist satisfaction. Conclusion: It is necessary to improve the quality of destination attributes at Borobudur Temple, promoting not only international tourists but also domestic tourists. It is also important to provide innovations that are expected to attract domestic tourists to make revisit when there are new things for them to experience